Hypertensive disorders of pregnancy - Ismawi, Hidayatul Radziah; Mohd Zainudin, Maizura; Jamani, Nurjasmine Aida (Malaysian Integrated Medical Professionals Association, 2022)
A World Health Organization (WHO) review identified hypertension as the main cause of maternal mortality in industrialised countries, accounting for up to 16% of maternal deaths. Hypertensive disorders of pregnancy are annually responsible for about 25,000 maternal deaths in Africa, 22,000 maternal deaths in Asia, 38,000 maternal deaths in Latin America and the Caribbean and 150 maternal deaths in industrialised countries.